Keterkaitan dan Pengaruh Peran, Kepribadian, dan Perilaku Gender dalam Kepemimpinan Perempuan - Dinafilah, Dena (Pusat Studi Gender dan Anak (PSGA) Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Sultan Maulana Hasanuddin Banten, 2025)
Women’s leadership has become an increasingly significant topic in the modern era, alongside the growing contributions of women in various sectors. This study explores the relationship between social roles, personality, and gender behavior in shaping the effectiveness of women’s leadership. Using a descriptive qualitative method through questionnaires distributed to respondents aged 18-45 years, the findings reveal that gender stereotypes and structural barriers still influence perceptions of women’s leadership. The results indicate that women tend to adopt transformational leadership styles that emphasize collaboration and empathy, although they are often perceived as less assertive compared to men. These findings highlight the importance of organizational culture reform and women empowerment strategies to create more inclusive gender equality in the workplace. This study provides insights into efforts to strengthen women’s participation in leadership at various levels.